2009
DOI: 10.35371/kjoem.2009.21.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Occupational Injuries and Health Problems for Some Female Workers in Non-standard Employment

Abstract: 박우진 1) •임형준 2) •원종욱 3) •고상백 4) •주영수 2) 노재훈 3) •오상용 1) •권영준 2) •황창국 1) •임정욱 1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For example, when the social support of female DSE workers was high, the number of MSCs was low. 39 The results showed that the risk of developing MSCs was lowered when the job resource level, such as quality of communication, was high. 22 In DSE workers, only job control played the role of moderating job resources, and skill discretion and participation analyzed in this study did not play a moderating role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when the social support of female DSE workers was high, the number of MSCs was low. 39 The results showed that the risk of developing MSCs was lowered when the job resource level, such as quality of communication, was high. 22 In DSE workers, only job control played the role of moderating job resources, and skill discretion and participation analyzed in this study did not play a moderating role.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, because the interaction term between MSCs and job control is negative, the indirect effect of MSCs, a health problem leading from job demands to presenteeism, was statistically significant. For example, when the social support of female DSE workers was high, the number of MSCs was low 39 . The results showed that the risk of developing MSCs was lowered when the job resource level, such as quality of communication, was high 22 …”
Section: Discussionmentioning
confidence: 99%